Use of Low Molecular Weight Heparin and Aminocaproic Acid in Chronic DIC Associated with Prostate Cancer- A Case Report - Keisuke Shirai; Uzair B. Chaudhary (The Scientific World Journal)
Disseminated Intravascular Coagulopathy (DIC) is the most common coagulopathy in patients with prostate cancer. Though rare, it could be fatal without treatment. Literature suggests that there is significant activation of fibrinolytic pathway. Pathophysiology of DIC in patients with prostate cancer is not completely understood. We present here a case of chronic DIC in a patient with metastatic androgen independent prostate cancer. His DIC was managed successfully with a combination of aminocaproic acid and low weight molecular heparin. The use of low molecular weight heparin may make management of chronic DIC in prostate cancer more feasible in an out patient setting.